Gestão empreendedora e Sistema Agroflorestal (SAF): o caso das guerreiras do assentamento Canudos, em Goiás - Ribeiro, Mariana (2023)
The adoption of Agroforestry Systems contributes to the socioeconomic and environmental development of family farming. In this context, rural women play an important and challenging role in ensuring food and nutritional security, agroecological practices and promoting territorial development. Although invisible, these women play an important role in domestic production and economy. The objective of this study was to evaluate the use of management strategies in the socioeconomic development of the AFS das Guerreiras de Canudos, of the Settlement Canudos, in Palmeiras de Goiás-GO. The research, of qualitative and quantitative nature, is analytical and descriptive, being conducted through action research. To obtain the data, bibliographical and documentary research was carried out, in addition to participatory rural diagnosis techniques, such as a questionnaire, semi-structured interview, analysis of the internal and external environments, and the elaboration of cartographic maps. The study showed that the adoption of management strategies has a positive impact on the socioeconomic development of women warriors, maximizing the benefits of AFS. It highlights the importance of valuing women's work, gender equity and the need for public policies that consider diversity in the context of women for rural development. It is suggested to deepen the discussion of the gender issue, its senses and disagreements, in the rural sphere, since it is women who suffer the most gender discrimination.